PROFIL EFIKASI DIRI PESERTA DIDIK BERDASARKAN PROSES DAN HASIL BELAJAR BIOLOGI SMA - Asih, Asti Dwi; Hasruddin, Hasruddin (UNIVERSITAS MUHAMMADIYAH METRO, 2023)
Self-efficacy is a psychological factor that can influence how well a person learns. Students' confidence in their abilities is proven to have a significant influence on learning outcomes. This research aims to describe students' self-efficacy profiles based on biology learning processes and outcomes. This research is descriptive research with a quantitative approach. The instruments used in data collection were questionnaires, observation sheets, and documentation. The population in this study were all students of class XI Science at SMA Negeri 21 Medan with a sampling technique using a total sampling method, totaling 143 students. The results of the research show that class category with a percentage of 67.1%, but biology learning outcomes are still in the poor category with an average score of 54.5. This shows that self-efficacy is only one of many factors that can influence student learning outcomes